The rabbit papillomavirus model: a valuable tool to study viral–host interactions. (8th April 2019) - Cladel, Nancy M.; Peng, Xuwen; Christensen, Neil; Hu, Jiafen
Abstract : Cottontail rabbit papillomavirus (CRPV) was the first DNA virus shown to be tumorigenic. The virus has since been renamed and is officially known as Sylvilagus floridanus papillomavirus 1 (SfPV1). Since its inception as a surrogate preclinical model for high-risk human papillomavirus (HPV) infections, the SfPV1/rabbit model has been widely used to study viral–host interactions and has played a pivotal role in the successful development of three prophylactic virus-like particle vaccines. In this review, we will focus on the use of the model to gain a better understanding of viral pathogenesis, gene function and host immune responses to viral infections. We will discuss the application of the model in HPV-associated vaccine testing, in therapeutic vaccine development (using our novel HLA-A2.1 transgenic rabbits) and in the development and validation of novel anti-viral and anti-tumour compounds. Our goal is to demonstrate the role the SfPV1/rabbit model has played, and continues to play, in helping to unravel the intricacies of papillomavirus infections and to develop tools to thwart the disease. This article is part of the theme issue 'Silent cancer agents: multi-disciplinary modelling of human DNA oncoviruses'.